2018
DOI: 10.1016/j.neuropharm.2017.08.018
|View full text |Cite
|
Sign up to set email alerts
|

Relative reinforcing effects of second-generation synthetic cathinones: Acquisition of self-administration and fixed ratio dose-response curves in rats

Abstract: "Bath salts" preparations contain synthetic cathinones which interact with monoamine transporters and function as either monoamine uptake inhibitors or releasers. 3,4-Methylenedioxypyrovalerone (MDPV), 3,4-methylenedioxymethcathinone (methylone), and 4-methylmethcathinone (mephedrone) were three of the most common cathinones (i.e., "first-generation" cathinones); however, after the US Drug Enforcement Administration placed them under Schedule I regulations, they were replaced with structurally related cathinon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
53
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(65 citation statements)
references
References 28 publications
12
53
0
Order By: Relevance
“…This study confirms that α-PVP is a highly effective reinforcer in female rats, just as has been previously shown in male rats (Aarde et al 2015a; Gannon et al 2017a). The potency and efficacy of α-PVP and the related drug MDPV (Figure 8) were similar in intravenous self-administration (IVSA) in female rats, just as in male rats (Aarde et al, 2015a).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This study confirms that α-PVP is a highly effective reinforcer in female rats, just as has been previously shown in male rats (Aarde et al 2015a; Gannon et al 2017a). The potency and efficacy of α-PVP and the related drug MDPV (Figure 8) were similar in intravenous self-administration (IVSA) in female rats, just as in male rats (Aarde et al, 2015a).…”
Section: Discussionsupporting
confidence: 91%
“…These compounds are highly effective and potent (e.g. in comparison with methamphetamine or methylone) reinforcers in male rats when assessed with the intravenous self-administration (IVSA) model (Aarde et al 2013; Schindler et al 2016; Watterson et al 2014), and MDPV and α-PVP have been shown to be approximately equipotent when directly compared under a Progressive Ratio schedule of reinforcement in IVSA (Aarde et al 2015a; Gannon et al 2017a). A binge-like acquisition pattern of MDPV IVSA has been previously reported for male rats (Aarde et al 2015b) in a study which also contrasted the effect of concurrent access to an activity wheel.…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4][5][6][7]), a growing number of synthetic cathinones have been reported to increase locomotor activity, produce cocaine-, methamphetamine-, or 3,4-methylenedioxymethamphetaminelike discriminative stimulus effects, and maintain intravenous self-administration (e.g., refs. [10][11][12][13][14][15][16][17][18][19]). For instance, we have recently shown that rats will acquire self-administration of the pyrrolidine-containing cathinones MDPV, MDPBP, MDPPP, α-PVP, and α-PPP at rates comparable to those observed with cocaine and that the potencies of these drugs to maintain responding under a fixed ratio (FR) 5 schedule of reinforcement are highly correlated with their potencies to inhibit uptake at DAT and NET but not SERT [13,16].…”
Section: Introductionmentioning
confidence: 99%
“…These compounds are highly effective and potent (e.g. in comparison with methamphetamine or methylone) reinforcers in male rats when assessed with the intravenous self-administration (IVSA) model Schindler et al 2016;Watterson et al 2014), and MDPV and α-PVP have been shown to be approximately equipotent when directly compared under a Progressive Ratio schedule of reinforcement in IVSA (Aarde et al 2015a; Gannon et al 2017a). A binge-like acquisition pattern of MDPV IVSA has been previously reported for male rats (Aarde et al 2015b) in a study which also contrasted the effect of concurrent access to an activity wheel.…”
Section: Introductionmentioning
confidence: 99%